2011
DOI: 10.1111/j.1469-8749.2011.03913.x
|View full text |Cite
|
Sign up to set email alerts
|

Medial gastrocnemius muscle volume and fascicle length in children aged 2 to 5 years with cerebral palsy

Abstract: MDF Maximum dorsiflexion MPF Maximum plantarflexion PCSA Physiological cross-sectional area AIM The aim of this article was to compare medial gastrocnemius muscle volume, physiological cross-sectional area (PCSA), muscle length, fascicle length, and pennation angle in children aged 2 to 5 years with spastic cerebral palsy (CP) and in typically developing children.METHOD Fifteen children with spastic CP (11 males, four females; mean age 45mo [SD 15mo]; five with hemiplega; 10 with diplega; 10 classified at Gros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
201
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(225 citation statements)
references
References 33 publications
17
201
3
Order By: Relevance
“…Consistent with previous findings in human patients (1, 2, 13), we found reduced maximal active forces of GA and PL in spastic rats. Loss of muscle volume has been reported in humans with spasticity (4,31,34,35) and, therefore, atrophy is believed to be the main cause of muscle weakness. In the present study, maximal active force of GA was decreased by 31%, whereas GA muscle mass was decreased by only 14%, albeit not significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous findings in human patients (1, 2, 13), we found reduced maximal active forces of GA and PL in spastic rats. Loss of muscle volume has been reported in humans with spasticity (4,31,34,35) and, therefore, atrophy is believed to be the main cause of muscle weakness. In the present study, maximal active force of GA was decreased by 31%, whereas GA muscle mass was decreased by only 14%, albeit not significantly.…”
Section: Discussionmentioning
confidence: 99%
“…23 Over the last decade, weakness has been increasingly recognised as a significant motor impairment, [22][23][24] purportedly affecting functional ability in children with CP. 25,26 A recent review of the literature on spastic CP found consistent evidence for small muscle size as indicated by reduced muscle volume, crosssectional area, thickness, and belly length in comparisons of paretic muscles with non-paretic and typically developing muscles. 24 Barber et al 25 described volumetric deficits of 22% in the medial gastrocnemii of young children (2-5y) with spastic CP compared with typically developing children.…”
mentioning
confidence: 97%
“…In their study, WillerslevOlsen et al demonstrate the important contribution of nonreflex mediated torque to muscle stiffness in the soleus muscle in CP, at a very young age. In line with this conclusion, Barber et al 3 have recently highlighted the altered gross morphology of the distal lower limb muscles in very young (2-5y) children with CP. These authors thereby challenge a prevalent view that the development of altered muscle structure is predominantly caused secondary to altered muscle behavior, such as hypertonia.…”
mentioning
confidence: 66%